Fluconazole in treatment of reccurent vaginal and vulvar candidiasis – literature review - Niemiec, Tomasz; Kajdy, Anna (Menopause Review/Przegląd Menopauzalny, 2009)
Vulvovaginal candidiasis is one of the most common reasons for seeking gynaecological care. Between 20 and 40% of all gynaecological visits are related to this problem. In the United States it is the second most common cause of vaginal infection. An important aspect of the problem is making the correct diagnosis based on appropriate clinical examination and available laboratory tests. The most common species found in both sporadic and recurrent vulvovaginal candidiasis is Candida albicans, although in recent years there has been a growing number of infections with non-albicans species. An ideal antimycotic drug should be easy to administer, effective in short therapy, with a broad spectrum of treatment, causing complete eradication, preventing recurrent infections, bringing relief to patients, without side effects, inexpensive and safe to administer during pregnancy. Sobol et al. proposed a long-term therapy to induce remission in recurrent vulvovaginal candidiasis. The proportion of women who had recurrent disease in the following months of observation was (respectively 6, 9, 12 months) 90.8%, 79.2% and 42.9% in comparison to the placebo group, 35.9%, 27.8% and 21.9%. The average time until recurrence in the fluconazole group was 10.2 months, while in the placebo group it was 4 months (p < 0.001). A lot of problems around the world related to antimycotic treatment results from the widespread use of over-the-counter drugs. In Poland this problem is not so common because antimycotic drugs without a doctor’s prescription are not so readily available. Use of over-the-counter drugs increases the number of resistant Candida species.